The Effectiveness of RIASEC cards game with Expressing Opinion Strategies for Developing Students' Career Adaptations - Luthfi, Anwar; Setiyowati, Arbin Janu; Probowati, Devy; Brahim, Juliana (Journal of Education for Sustainability and Diversity, 2024)
Career adaptability is a person's ability to adapt to unexpected situations and career changes, determine a career that is in accordance with interests and abilities, and be able to carry out roles and responsibilities for the chosen career. This study aims to examine the effectiveness of the RIASEC cards game with the strategy of expressing opinion in group guidance to develop students' career adaptability. The research design uses a quantitative approach, the type of experimental research is one group pretest-posttest design. Data collection was carried out on class XI IPS 2. The instrument used is the career adaptability scale adapted from Hidayati. From the results of the pretest, 8 students were taken as research subjects using a purposive sampling method, with low, medium, and high career adaptability ability categories. The treatment of group guidance services was carried out 5 meetings outside of the pretest and group formation. The analysis technique used the Wilcoxon Test with the results that Ha was accepted, so it was concluded that the RIASEC cards game with the expressing opinion strategy in group counseling is effective for developing career adaptability for class XI students of SMA Islam Al Ma'arif Singosari.